Pengembangan Buku Cerita Anak Berbasis Sosio-Budaya Sebagai Upaya Pendidikan Karakter Berkelanjutan Bagi Peserta Didik SD Se-Kota Madiun - Arielia Yustisiana; Wenny Wijayanti (JURNAL ASIMILASI PENDIDIKAN, 2026)
Literacy is still a topic that resonates in the world, especially in the scope of education. Various efforts were made by the government to provide the program, one of which was through the School Literacy Movement. To support the program, efforts need to be made to increase children's literacy motivation. One of the efforts made is to develop storybooks that interest students. In addition to increasing interest in reading, storybooks can be used as a means of character education. Through the stories presented, students can learn the concrete experienced. So far, there are not many books presented that contain values that can be learned by students, so it is necessary to develop storybooks for children that are socio-cultural-based Efforts to maintain local and social culture are built in line with the Sustainable Development Goals (SDGs), particularly SDG 4 on Quality Education. Character education for elementary school students must start from early childhood, aiming to embed foundational values such as mutual cooperation, creativity, and respect for diversity, so that students can implement them in everyday life. In addition, children's story books are considered effective in teaching existing learning content to students. Learning to use children's storybooks is also more in line with the characteristics of elementary-age children who are in the concrete operational stage. In the story, students will be faced with a story that can be directly related to their life or experience in the real world. Values and learning materials can be revealed by utilizing the play, setting, or storyline in it. With the research, the development of this storybook is expected to make a positive contribution to the development of literacy and character of students. Developing storybooks with socio-cultural content is the purpose of this research, so the results of this research are packaged in the form of storybooks that can be used by schools.